Heavy metal analysis in fish muscle at plant retention pond: article - Mohd Ariff, Nur Shafika Amilia; Ismail, Kamariah Noor (2017)
The aim study for this project is to analyse the heavy metal uptake in different part fish of Anabas Testudenius by using Inductively Coupled Plasma (ICP-OES). There were several heavy metals that have been examined in this study which is Arsenic, Chromium, Copper, Iron, Zinc and Manganese. This sample of fish was weighted for every four week and their weight has been checked while leave them at the plant retention pond for two month. Then, the Anabas Testudenius has been divided into three parts which is head, body and lastly is tail. The finding of this data has been evaluated by using Microsoft Excel. The part that has lowest value of heavy metal is a tail part with 1.1731 ppm concentration of iron for tail of Fish 3, 1.2868 ppm concentration of zinc for tail of Fish 2 and zero reading for heavy metal of arsenic. Based on the data that has been analysing, mostly part of head has highest value for each types of heavy metal. It shows that the part of head is most dangerous part because it easily contaminated will all types of heavy metal except copper on this experiment.